Neue Forschungen zu Glashandwerkern unter den Karolingern und ihren Nachfolgern (8. bis 10. Jahrhundert) - Zimmermann, Martin (2023)
So far, the history of early Medieval glassmakers has mainly been derived from archaeological sources. Significant in this context was, more than half a century ago, the discovery of a new glass recipe, which began to spread in Europe from the ‘deepest’ early Middle Ages; the question of how this could develop is still subject of various discussions. A new contribution was published by Alexis Wilkin in 2019. According to this contribution, the early Medieval glass artisans owed the technological foundations of their new recipe to their collaboration with metal artisans. There is some clear evidence for this theory, but besides the technical innovation the social conditions of the artisans should not be forgotten. The glassmakers of the early Middle Ages were not free entrepreneurs, in the historical texts they are dependent on their landlords. This dependency, however, gives rise to a purely historical method of investigation: new finds of early Medieval glassworks manufactured according to the altered glass recipe can be assigned to the territories of specific landlords. This paper examines the extent to which family connections can be made visible in the passing on of glassmakers belonging to these families, perhaps also in the development of the new glass recipe.